2021
DOI: 10.3168/jds.2020-19625
|View full text |Cite
|
Sign up to set email alerts
|

Fermented milk with Lactobacillus curvatus SMFM2016-NK alleviates periodontal and gut inflammation, and alters oral and gut microbiota

Abstract: This study aimed to analyze the effect of milk fermented with Lactobacillus curvatus SMFM2016-NK on periodontal diseases and gut health in a rat model. To improve the effect of Lb. curvatus SMFM2016-NK-fermented milk administration for relieving periodontitis, the periodontitis rat models were treated with the following for 4 wk: 10% skim milk (normal), periodontitis + 10% skim milk (negative control), periodontitis + Lactobacillus rhamnosus GG-fermented milk (positive control), and periodontitis + Lb. curvatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Superoxide dismutase and glutathione peroxidase are some of the enzymes that constitute the antioxidant system and play a key role in the cellular stress regulation. [43][44][45] Although our study is the first experimental study on probiotics to immunohistochemically emphasize such antibodies in a model of periodontitis and DM, Araújo et al 4 showed in an isolated periodontitis model that increased SOD and GPx were also detected in the periodontitis groups. However, as in our work, Met helped to decrease them similarly to the control groups.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Superoxide dismutase and glutathione peroxidase are some of the enzymes that constitute the antioxidant system and play a key role in the cellular stress regulation. [43][44][45] Although our study is the first experimental study on probiotics to immunohistochemically emphasize such antibodies in a model of periodontitis and DM, Araújo et al 4 showed in an isolated periodontitis model that increased SOD and GPx were also detected in the periodontitis groups. However, as in our work, Met helped to decrease them similarly to the control groups.…”
Section: Discussionmentioning
confidence: 69%
“…An in vivo study observed that this probiotic effectively suppressed bone loss in a mouse model of induced periodontal disease 21 . Likewise, clinical studies in humans have demonstrated improvements in periodontal parameters after the use of this probiotic, suggesting that its use may be beneficial in reducing pathogenic bacteria and/or serving as an anti‐inflammatory adjuvant 22,23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of L. gasseri CECT5714 increases the production of SCFAs in the intestine (Olivares et al, 2006) and SCFAs exert anti-inflammatory effects by modulating the levels of PGE, cytokines, and chemokines (Cox et al, 2009). In addition, consuming fermented milk containing L. crispatus SMFM2016-NK can effectively reduce the expression levels of intestinal TNFα and IL-1β (Choi et al, 2021). Therefore, L. gasseri TM13 and L. crispatus LG55 may also exert their effects on the improvement of vaginal health by reducing systemic inflammation through immunomodulatory effects in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that PMB regulates periodontal disease. Recent research presented that an administration of fermented milk using Lactobacillus curvatus to periodontitis-induced mice leads to a significant decrease of the expression levels of inflammatory cytokines in the oral gingiva tissue and colon tissue compared to control group ( Choi et al, 2021 ). Also, randomized clinical trial was performed to confirm the effect of PMB with fermented bovine milk in periodontal disease, and papillary-marginal-attached index, gingival index, and probing depth score of the experimental group showed greater tendency than those of placebo group ( Oda et al, 2019 ).…”
Section: Probiotics-mediated Bioconversion (Pmb) and Periodontitismentioning
confidence: 99%